2011
DOI: 10.1111/j.1399-6576.2011.02490.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic effect of aprotinin during craniosynostotic surgery in children

Abstract: Blood loss and need for blood transfusion were significantly reduced in the aprotinin group. No allergic or other possible aprotinin-specific complications were registered in the aprotinin group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…However, the subgroup analysis on randomized controlled trials showed that patients in the TXA group did not have significantly reduced blood loss during surgery compared with patients in the placebo group (p = 0.14). 7 In the current study, only 10% of patients in the TXA group received PRBCs after the operation, a rate that was lower than the rate observed in a previous study by Ongun et al (23.5%) 14 and higher than the rate reported in a study by Goobie et al (0%). 8 The postoperative EBV loss after 8 hours was significantly lower in the TXA group than in the control group, as similarly shown by Goobie et al (median 3 ml/kg vs 12 ml/kg); 8 however, the difference was not significant in other previous studies.…”
Section: Effect Of Txa On Blood Loss and Transfusion In Craniosynosto...contrasting
confidence: 71%
See 4 more Smart Citations
“…However, the subgroup analysis on randomized controlled trials showed that patients in the TXA group did not have significantly reduced blood loss during surgery compared with patients in the placebo group (p = 0.14). 7 In the current study, only 10% of patients in the TXA group received PRBCs after the operation, a rate that was lower than the rate observed in a previous study by Ongun et al (23.5%) 14 and higher than the rate reported in a study by Goobie et al (0%). 8 The postoperative EBV loss after 8 hours was significantly lower in the TXA group than in the control group, as similarly shown by Goobie et al (median 3 ml/kg vs 12 ml/kg); 8 however, the difference was not significant in other previous studies.…”
Section: Effect Of Txa On Blood Loss and Transfusion In Craniosynosto...contrasting
confidence: 71%
“…The median values of blood loss and requirement for blood transfusion during the operation decreased from 22% to 3.9% and 21.1% to 0%, respectively, in the treatment group compared with the control group (p < 0.001). 7 While a similar study had shown that estimated blood loss was not significantly lower in the aprotinin group, this study also showed that the intraoperative and first 3-day postoperative rates of blood transfusion were significantly lower in the aprotinin group (32 vs 52 and 33 vs 57 ml/kg, respectively, p = 0.03). 11 According to Ahmed et al in 2014, administration of aprotinin for pediatric craniofacial surgeries resulted in significantly less colloid administration and blood transfusion in the aprotinin-treated group (p < 0.003).…”
Section: Effect Of Aprotinin On Blood Loss and Transfusion In Cranios...mentioning
confidence: 41%
See 3 more Smart Citations